Association of the immunogenicity of intramuscular SARS-CoV-2 mRNA vaccination with computed tomography muscle images in patients with muscular disorders - Naka, Tomoaki; Funato, Michinori; Yasuda, Kunihiko; Nakayama, Takahiro; Kuru, Satoshi (Frontiers in Immunology, 2024)
BackgroundsIntramuscular mRNA vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have a low intensity and latency of antibody response in patients with muscular disorders (MDs). However, the mechanisms involved in this phenomenon remain unknown. This study aimed to clarify the mechanism of the low immunogenicity of intramuscular SARS-CoV-2 mRNA vaccination in patients with MDs.MethodsWe evaluated 44 individuals, including 23 patients with MDs and 21 patients without MDs. The median age of the patients was 39 years (range 20–63 years). The anti-SARS-CoV-2 spike protein receptor-binding domain (S-RBD) IgG levels from a previous study were reused. Mean computed tomography (CT) values and areas of the deltoid muscle from CT images were measured, and they were compared with the anti-SARS-CoV-2 S-RBD IgG levels.ResultsOne month following the second vaccination, the antibody response among patients with MDs showed a low tendency compared with that among patients without MDs. Surprisingly, a similar pattern was observed when comparing mean CT values. Patients with mean CT values of zero HU and lower had a lower tendency of antibody response after the intramuscular administration of SARS-CoV-2 mRNA vaccines.ConclusionThe low immunogenicity of intramuscular SARS-CoV-2 mRNA vaccination against MDs may be mainly affected by disease type and MD pathogenesis. However, SARS-CoV-2 immunization in patients with MDs warrants further investigation.